Form of a project organization and project team subculture - Kamiński, Robert (Wybrane aspekty zarządzania procesami, projektami i ryzykiem w przedsiębiorstwach, 2020)
The article discusses cultural determinants of project management. Its purpose is to discuss the subculture of the project team and analyze the impact of the form of project organization on its formation. It was shown that the uniqueness of each project and its unique nature in a given organization make it impossible to formulate a coherent list of standards and values of the project team’s subculture. Based on the forms of project organizations described in the literature, their influence on the strength of the project team’s subculture was determined, the research hypothesis was formulated and verified based on empirical research. The summary includes the most important conclusions and further research perspectives.